Microstructural evolution in solution heat treatment of gas- atomised Al alloy (7075) powder for cold spray - Sabard, Alexandre; Lovelock, H.L. de Villiers; Hussain, Tanvir (Springer, 2017)
Cold gas dynamic spray is being explored as a repair technique for high-value metallic components, given its potential to produce pore and oxide-free deposits of between several micrometers and several millimeters thick with good levels of adhesion and mechanical strength. However, feedstock powders for cold spray experience rapid solidification if manufactured by gas atomization and hence can exhibit non-equilibrium microstructures and localized segregation of alloying elements. Here, we used sealed quartz tube solution heat treatment of a precipitation hardenable 7075 aluminum alloy feedstock to yield a consistent and homogeneous powder phase composition and microstructure prior to cold spraying, aiming for a more controllable heat treatment response of the cold spray deposits. It was shown that the dendritic microstructure and solute segregation in the gas-atomized powders were altered, such that the heat-treated powder exhibits a homogeneous distribution of solute atoms. Micro-indentation testing revealed that the heat-treated powder exhibited a mean hardness decrease of nearly 25% compared to the as received powder. Deformation of the powder particles was enhanced by heat treatment, resulting in an improved coating with higher thickness (* 300 lm compared to * 40 um for untreated feedstock). Improved particle–substrate bonding was evidenced by formation of jets at the particle boundaries.